Enterobius vermicularis: A Controversial Cause of Appendicitis - "Gh Mowlavi; J Massoud; I Mobedi; M Rezaian; S Solaymani Mohammadi; NE Mostoufi; MJ Gharaguzlo" (Tehran University of Medical Sciences, 2004)
Enterobiasis is undoubtedly one of the most common human helminths infections through the world, with an estimate of 1000 million cases worldwide. Although adult worms and their eggs are frequently found in inflamed appendices, but the role of the parasite in producing appendicitis in humans still remains controversial. Although acute appendicitis may occur at any age, but it is relatively rare at the extremes of age. A histopathological study of infested appendices with Enterobius vermicularis was performed in Khuzestan province, south western Iran, during 2001 to 2003. All 40 samples had surgically been removed during the emergency operations and histopathological process with (H&E) staining has been performed for each. One of the main objects of this work was to collect more data about the possible role of this highly prevalent human round worm as a causative agent of appendicitis in humans, leading to different types of appendicitis in this part of the country. In this occasion over the slide examinations of the tissue sections, fewer cases than expected, with worm infested appendices were seen exclusively affected with this parasite.